INTERPERSONAL RELATIONS IN GYMNASTICS ACTIVITIES AT SCHOOL (Fiep Bulletin - online, 2017)
Physical Education must promote the motor skill learning during the school time, when children and adolescents arestudying, giving important experiences for the intellectual and physical development. Further then this, in the classes happenrelevant didactical experiences among the students with the interpersonal relations promoted with activities interaction andparticipation, establishing social-cognitive acquisitions, powering the social living, discipline and affective. This study has had theobjective to identify the interpersonal relations with the employ of different gymnastics activities in Physical Education Classes,with students among six to fourteen years old from Luciano Corsetti Public Elementary School in Caxias do Sul city, during theScholar Gymnastics Activities traineeship, in two week meetings with one hour of work time. The study involved the first gradeand the seventh grade of Elementary School, with 24 and 30 students regularly registered. As instrument, it has been used theparticipative observation in the traineeship classes, with ethnography research style, where interpersonal moods were analyzedwhile the gymnastics activities at Physical Education classes were happening. Motivation, discipline, respect and good mannershave been found as activities integration ways, showing the didactic importance of Gymnastics in School.